2007
DOI: 10.1111/j.1471-0528.2006.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function and satisfaction in heterosexual couples when men are administered sildenafil citrate (Viagra®) for erectile dysfunction: a multicentre, randomised, double‐blind, placebo‐controlled trial

Abstract: Objective  To investigate the effect of improvement in erectile dysfunction (ED) on sexual function and satisfaction measures in heterosexual couples in which the woman reports that sexual intercourse is unsatisfactory at least half of the time. Design  Multicentre, double‐blind, placebo‐controlled study. Setting  Outpatient medical clinics. Population  Hundred and eighty men with ED and their female partners in whom sexual intercourse was satisfactory about half the time or less (score of ≤3 on the Female Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 19 publications
7
56
1
Order By: Relevance
“…Even life satisfaction was lower among the females whose partners experienced ED. Similar findings were obtained by Heiman et al 23 who found that postmenopausal females (n ¼ 85) whose partners were treated for ED (compared with 91 females whose partners received a placebo) showed improvements in their sexual function, sexual satisfaction, and treatment satisfaction. Finally, Fisher et al 22 showed that the frequency of orgasm, sexual activity, and sexual satisfaction was lower among females whose male partners experienced ED.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Even life satisfaction was lower among the females whose partners experienced ED. Similar findings were obtained by Heiman et al 23 who found that postmenopausal females (n ¼ 85) whose partners were treated for ED (compared with 91 females whose partners received a placebo) showed improvements in their sexual function, sexual satisfaction, and treatment satisfaction. Finally, Fisher et al 22 showed that the frequency of orgasm, sexual activity, and sexual satisfaction was lower among females whose male partners experienced ED.…”
Section: Introductionsupporting
confidence: 87%
“…These primarily focused on the cost of the medication, the side effects, pressure on them to perform as well as the lack of spontaneity that may result from the use of the medication. 18,13,22,23 This study shows that the main motives for females seeking treatment for their partner's ED primarily center on their partner's needs rather than their own level of s.d. The other major motive was to improve the level of intimacy and communication in their relationship.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, a study assessing the impact of successful treatment of PE on the partners sexual dysfunction would be very interesting, and hopefully as successful as seen in treating women's sexual dysfunction when treating the man for his ED. 14,[16][17][18][19][20] The results of the PEP-SI, SQOL and SRS indicate that the partners of men with PE have higher rates of negative emotional impact and dissatisfaction with sex. In addition, the female partners of men with PE demonstrate a lower perception of sexual quality of life and a poorer sexual relationship with their partners than the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Of course, these figures only represent the women and partners who agreed to take part in the study and there is no indication of the timing of the onset of the men's or women's sexual dysfunction and, therefore, no clarity as to which preceded or accompanied which. However, lending support to the theory that a woman's sexual difficulties can be contingent on her partners are a number of studies showing that the sexual functioning of women with partners who have ED improved significantly when the man's ED was treated with a phosphodiesterase type 5 inhibitors (PDE5i) 16 and, specifically, with sildenafil 14,17,18 or vardenafil. 19 Althof et al 20 reported improvements in women's sexual function when her partner's ED was treated with selfinjection or vacuum therapy, and Cayan et al 14 reported the same with ED treatment of penile prosthesis implantation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the social and psychological challenges that come with aging, including those related to more general deteriorating health or to specific health problems -of oneself and/or of one's partner -as well as reduced independence and mobility, may result in or exacerbate already existing stress, depression, or loneliness, factors that all have been associated with sexual problems in men (Atlantis & Sullivan, 2012;Latini et al, 2006;Martin et al, 2012). Also, sexual dysfunctions in men are not uncommonly associated with problems with sexual function of their partner (Heiman et al, 2007;Jiann et al, 2013). Although individual-as well as dyad-based variability in how well one copes with such challenges and changes can be assumed to influence the likelihood that one may experience problems with one's sexual function (including desire for sex), little research exists on the relevance of dyadic processes and adjustment to (stability or change in) sexual function over the life course.…”
Section: Aging Men's Sexual Problemsmentioning
confidence: 99%